Preparation and Characterization of Glass-Fiber-Reinforced Modified Polyphenylene Oxide by a Direct Fiber Feeding Extrusion Process - SeungJae Ahn; Jae-Chul Lee; Ki-Young Kim (Applied Sciences, 2021)
Polyphenylene oxide (PPO) polymers have good mechanical, electrical, and thermal properties, but they have poor processability owing to their quite high melt viscosity. This hinders the manufacturing processes of fiber-reinforced thermoplastics that have enhanced mechanical and physical properties. Although PPO was modified by blending with polystyrene (PS) or polyamide to improve processability, the modified PPO (mPPO) still had a high melt viscosity compared with other polymers. Thus, the fiber-reinforced mPPO is manufactured by compounding with chopped fiber, while various methods are applied to manufacture the fiber-reinforced polypropylene and polyamide in order to improve properties. One of the methods is a direct fiber feeding method, which can keep the longer fiber length because of a direct and continuous roving yarn feeding without chopping. Therefore, the composite manufactured by the direct fiber feeding method is expected to improve the mechanical properties. Hence, this study aims to investigate the feasibility of a direct fiber feeding extrusion process for manufacturing glass-fiber-reinforced mPPO or GFmPPO. The manufactured GF/mPPO composites exhibited increased tensile and flexural properties as the fiber content increased up to 50 wt% of GF owing to the predominant effects of fiber content. Nevertheless, the larger core area in the cross-section micrograph of the tensile specimen of the GF/mPPO composite with 50 wt% of GF was observed to reduce the fiber efficiency factor for tensile strength. Meanwhile, the impact strength of the GF/mPPO composites decreased with increasing GF content. This is attributed to the insufficient fiber length for the impact strength. As the GF content increased, the glass transition temperature slightly decreased. This result was interpreted as being a result of thermal degradation during the extrusion process to manufacture the GF/mPPO masterbatch. The results of the dynamic mechanical analyses, e.g., storage modulus and tan δ, show the good correlation with the increased flexural modulus, the decreased glass transition temperature, and the impact strength as the GF content increased.